Coming to care : The work and family lives of workers caring for vulnerable children - Brannen, Julia (Book collections on Project MUSE., 2007)
Public social services are increasingly being individualised in order to better meet the differentiated needs of competent and independent citizens and to promote the effectiveness of social interventions. This book addresses this development, focusing on a new type of social services that has become crucial in the 'modernisation' of welfare states: activation services. The book discusses and analyses the individualisation of activation services against the background of social policy reforms on the one hand, and the introduction of new forms of public governance on the other. Critically discussing the rise of individualised social services in the light of various theoretical points of view, it analyses the way in which activation and the 'active subject' are presented in EU discourse. It compares the introduction of individualised activation services in five EU welfare states: the UK, Germany, Italy, Finland and the Czech Republic, focusing on official policies as well as policy practices. The book provides original insights into the phenomenon of the individualised provision of activation services. It is useful reading for policy makers as well as for students and researchers of welfare states, social policies and public governance.